Evaluation the Effectiveness of E-Learning Platforms in Developing Students’ Geographic Skills - المجلسي م. م وفاء محمد مهدي المجلسي (Journal of College of Education, 2023)
The current research aims to evaluate the effectiveness of e-learning platforms in developing students’ geography skills, and to achieve the goal of the research, the null hypothesis was developed, and the current research is determined by a sample of literary quarter students for the academic year 2022-2023. And the community adopted a sample for the study, the researcher rewarded the students of the two research groups statistically by using the t-test for two independent samples in the variables: chronological age calculated in months, previous experience, parental achievement, intelligence), and she prepared an achievement test, and its stability, validity, discriminatory power, and paragraph difficulty coefficients were calculated, and differences were found It is statistically significant between the mean scores of achievement for the students of the two research groups, and for the benefit of the students of the experimental group who studied geography using the e-learning strategy method. In light of the results of the current research, the researcher concluded a number of conclusions and recommendations.